1967
DOI: 10.1090/qam/99884
|View full text |Cite
|
Sign up to set email alerts
|

A physical basis for the generalized gamma distribution

Abstract: Introduction.A number of known families of probability distributions can be derived from requirements that are physical in the sense that they describe the random behavior of the event under consideration. The Poisson process is typical of these: If X{t) is equal to the number of occurrences of a specified event in the interval [0, t), then one can show that X (t) has, for each t, a Poisson distribution, if the probabilistic behavior of the event satisfies a few very simple physical requirements [1], The norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 6 publications
2
79
0
Order By: Relevance
“…It is referred in the literature as the three-parameter Generalized Gamma function [42]. Dumouchel [40] demonstrated that it is identical to the empirical Nukiyama-Tanasawa distribution, which is an empirical distribution often used in the literature to represent liquid spray drop-diameter distribution.…”
Section: G(d) = Cte Equation 59 Is Identical To Cousin Et Al's Somentioning
confidence: 99%
See 1 more Smart Citation
“…It is referred in the literature as the three-parameter Generalized Gamma function [42]. Dumouchel [40] demonstrated that it is identical to the empirical Nukiyama-Tanasawa distribution, which is an empirical distribution often used in the literature to represent liquid spray drop-diameter distribution.…”
Section: G(d) = Cte Equation 59 Is Identical To Cousin Et Al's Somentioning
confidence: 99%
“…Dumouchel [40] proposed an extension of Cousin et al's formulation [31] addressing the question of the small drop diameter distribution. This extension was inspired by Griffith [41] and Lienhard and Meyer [42]. The most objective distribution that satisfies the constraint introduced by Cousin et al (Equation 47) is the one that maximizes the statistical entropy (Equation 16).…”
Section: Reports a Constant Distribution F N (D) And The Maximizationmentioning
confidence: 99%
“…24.6). According to several authors (e.g., Stacy, 1962;Lienhard and Meyer, 1967;Patriarca et al, 2004;Chakraborti and Patriarca, 2008;Khodabin and Ahmadabadi, 2010;Lallouache et al, 2010;Melker et al, 2010), M-BD v can be seen as a particular case of generalized standard gamma distribution. This indicates that; if it is possible to assign a consistent dual meaning (thermostatistical as well as ecological) to any indicator that fits gamma distribution; then it is plausible to model such an indicator by means of an extension of the M-BD v to a given macroscopic system (a taxocenosis, in this case).…”
Section: Nmentioning
confidence: 99%
“…Let us consider the Instantaneous Unit Hydrograph (IUH) of a basin, expressed as a function of time, f(t) (Lienhard and Meyer, 1967):…”
Section: River Network Fractal Dimensions and Hydrologic Responsementioning
confidence: 99%